PENAKSIR RASIO UNTUK VARIANSI POPULASI MENGGUNAKAN KUARTIL DARI KARAKTER TAMBAHAN PADA SAMPLING ACAK SEDERHANA - Asri Elvita; Arisman Adnan; Haposan Sirait (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This paper discusses three ratio estimators for population variance in simple randomsampling using quartiles of the auxiliary variable given by Subramani andKumarapandiyan [International Journal of Statistics and Applications., 2(5): 67-72].The estimators discussed are the ratio estimator using the first quartile, the third quartileand the inter-quartile range. These three estimators discussed are biased estimators.Furthermore, their mean square errors are compared to show which one is the mostefficient estimator. This comparison shows that the ratio estimator using inter-quartilerange is the most efficient estimator.